Tajikistan - Second Programmatic Public Expenditure Review : Volume 1. Main Report - World Bank (2012)
This report, Second Programmatic Public Expenditure Review (PPER 2), is a sequel to PPER, which was published in July 2007. PPER 2 provides a detailed analysis of key public expenditure issues in Tajikistan and reports on the nonlending policy dialogue and technical assistance programs managed and coordinated by the World Bank. PPER 2 has a special focus on social sectors, especially the health and education sectors. Public Expenditure Tracking Surveys (PETS) carried out for the first time in Tajikistan in 2007 contributed to the findings in this report. The report also updates the macroeconomic and fiscal situation to take account of important developments in 2007 and analyzes the implications of energy sector reforms and investments for fiscal sustainability. This report is intended to contribute to improving the quality of life in Tajikistan through a comprehensive reform program. It spells out the macroeconomic, energy, and budget reforms necessary to achieve the growth the country seeks and, at the same time (and frequently via the same measures) the social welfare targets of the Millennium Development Goals (MDGs).